2020
DOI: 10.9734/ajrb/2020/v7i230135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Associated Changes on Haematological Profile of Wistar Rats Fed Curcuma longa (Turmeric) Rhizome Powder

Abstract: Turmeric spice has a diverse array of biological activities. The present study evaluated body weight and haematological impact of Curcuma longa (Turmeric) in male albino rats using  standard analytical methods. Twenty four healthy male albino rats were used for the study.  Results shows no significant increase in body weight in the first week of dieting while a gradual increase     was observed with increasing weeks of dieting.  Treatment with the powder did not significantly (P ≥ 0.05) alter the levels of hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
3
1
Order By: Relevance
“…The mean value of MCV in this current study was within normal rang thus indicated the absence of microcytic anaemia, a condition in which the red blood cells (erythrocytes) contain less hemoglobin and are usually also hypochromic, meaning that the red blood cells appear paler than usual [46]. This is in contrast to the reported of Iwueke et al [35] who observed slight reduction in MCV level of rat treated with turmeric powder. The correlation in the increase pattern of PCV and MCV in this study indicate production of healthy RBC [47,48] The increase level of WBC, Lymphocytes and granulocytes in rats fed with STBH although not above the basal, reflect its immunostimulatory potential.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The mean value of MCV in this current study was within normal rang thus indicated the absence of microcytic anaemia, a condition in which the red blood cells (erythrocytes) contain less hemoglobin and are usually also hypochromic, meaning that the red blood cells appear paler than usual [46]. This is in contrast to the reported of Iwueke et al [35] who observed slight reduction in MCV level of rat treated with turmeric powder. The correlation in the increase pattern of PCV and MCV in this study indicate production of healthy RBC [47,48] The increase level of WBC, Lymphocytes and granulocytes in rats fed with STBH although not above the basal, reflect its immunostimulatory potential.…”
Section: Discussioncontrasting
confidence: 74%
“…The present study shows that the administration of the herbal mixture at low dosage (0.65mg/g) has high improvement in the body weight of the rats compared to the control. Iwueke et al [35] stated that intake of Curcuma longa at different concentrations may improve metabolic status through balancing of basal metabolic rate, which may in turn cause increased energy intake. The weight gain in experimental animals in this study therefore is attributed to high nutritional value of the herbal mixture, digestibility and acceptability of the herbal mixture by animals as well as presence of non-toxic compounds in the food [35].…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cell and hemoglobin function in the efficient transport of oxygen into and carbon dioxide out of, the body and in concert with PCV (the percentage of RBC in blood) indicates oxygencarbon dioxide balance status Oyedeji and Bolarinwa, 2013;Ugwuene, 2011). Furthermore, although non-significant influence on rats' hemoglobin and RBC levels but slight reduction in packed cell volume (PCV) concentration, were interpreted as absence of adverse effect on the rats' hematological properties (Iwueke, et al, 2018); Agiang, et al (2017) associated possession of some anti-anemic properties following improved/elevated RBC, Hb and PCV. Thus, the significant elevation in the levels of RBC, HB and PCV of the rats following exposure to bitter leaf stem extract as reported herein could be indicating improved gaseous (oxygen and carbon dioxide) transport leading to favorable oxygen -carbon dioxide balance, and improved anti-anemic properties in the rats.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent similar study, bitter leaf stem extract exhibited potent antifungal activity without altering serum electrolytes in MSGintoxicated rats' (Nwankwo, et al, 2019). In particular, changes in hematological properties highly predicted animal toxicity (Chike, et al, 2018) and hematological parameters, including red blood cells (RBC) count, hemoglobin (HB) concentration and packed cell volume (PCV), determined herein served as important indices of physiological and pathological status in animal studies (Iwueke, et al, 2018;.…”
mentioning
confidence: 99%